The impact of the actual existence of the commercial company on partners and third parties - Researcher: Mohammed Hamad Abdullah Al-Sarhan (The college of law and political science journal, 2023)
This study aims to demonstrate the effects of recognizing the theory of the actual company, and the consequences of recognizing it in terms of effects on third parties and partners, and protecting this third party who has dealt with the company and is not aware of the legal existence of this company.Where the following problem arises: the extent to which the Jordanian legislator recognizes the apparent legal positions resulting from the commercial company in the event that one of the pillars of its establishment is disturbed, and the extent to which it recognizes the legal effects of the invalidity in relation to the actual company, and the extent to which it recognizes the retroactive effect of the actual company and its legal effects for third parties and partners.The study concluded that the actual company is an existing company and actually exercises its activity on the ground, but it was exposed to a defect in one of its substantive or private general pillars or one of the formal pillars. Partners.The study recommends that recognition be made explicitly by the Jordanian legislator of the actual company in all types of companies in a way that facilitates the work of the judiciary and without entering into different interpretations or jurisprudence, and without fear of invalidity or any delay that causes harm to any party in the company or others